Adoption of GSCM Practices and Sensitivity/influencing Factors: An Empirical Study at the Moroccan Firm Level - Amrani Souhli, Khaoula; En-nadi, Abdelali (International Journal of Industrial Engineering and Management, 2023)
GSCM (Green Supply Chain Management) is a concept that aims at the environmental dimension of sustainable development. Many factors influence the decision to adopt a green strategy, which is also an important indicator in determining the adoption level of its practices. In this article, based on a literature review, we propose a theoretical model that shows a hypothesis on the relationship between ten sensitivity factors and the level of adoption (LA) of GSCM practices (GSCMPs). Using the linear multiple regression method on collected data from a survey of Moroccan companies, we confirmed or invalidated the relationships in our model. Finally, we retained the operational model that shows the impact of the two main factors on the approval of GSCM practices: the importance of early adoption of environmental practices (EAEP) and top management commitment (TMC). Organizations can use this model to improve their GSCM practices and enhance their LA. The analysis results can also provide insights for future research on GSCM and LA. Article history: Received (November 23, 2022); Revised (June 22, 2023); Accepted (July 5, 2023); Published online (July 20, 2023)